Determination of amino acid composition and biological value in protein-berry concentrates - Grek, Olena; Pshenychna, Tetyana; Onopriichuk, Olena; Tymchuk, Alla (My University, 2019)
Research of the amino acid composition of proteins, including the content of free and fixed amino acids, and biological value in protein-berry concentrates, obtained by thermo acid coagulation are an actual direction. Proteins in concentrates have a full amino acid composition and contain all essential amino acids, the content of which from amounts are 41.97% and 43.96%, respectively, for protein-berry and milk-protein concentrates. The total content of amino acids in protein-berry concentrates increased by 20.18% compared to the control sample - through the active coagulating effect of organic acids blackcurrant paste. Актуальним є дослідження амінокислотного складу білків, у тому числі вмісту вільних і зв’язаних амінокислот та біологічної цінності в білково-ягідних згустках, отриманих термокислотним способом осадження. Встановлено, що білки згустків мають повноцінний амінокислотний склад і містять всі незамінні амінокислоти, вміст яких від загальної суми становить для білково-ягідних та молочно-білкових – 41,97 % та 43,96 % відповідно. Загальний вміст амінокислот в білково-ягідних згустках збільшився на 20,18 % порівняно з контролем – за рахунок активної коагулюючої дії органічних кислот чорносмородинової пасти.
Keywords: concentrate; coagulation; amino acids; концентрат; коагуляція; амінокислоти; кафедра технології молока і молочних продуктів